Perspectives (of People of Color) on Psychological Science: Does Psychological Science Listen?. Issue 2 (June 2023) - Desai, Miraj U; Laubscher, Leswin; Johnson, Spencer
It remains to be seen whether the American Psychological Association's new apology and resolutions on racism will help redress longstanding inequities in the field. To be sure, critiques of psychological science vis-à-vis racism have been around for decades, despite being ignored by psychological science, even when spoken by Dr. King—in his profound meditation on science, psychology, and racism in a speech delivered to the APA—or by psychiatrist Frantz Fanon—who has had a foundational influence on the broader history of anti-racism scholarship but remains relatively disregarded in his own psy-fields. This article addresses the viewpoints of these and other people of color on psychological science, which have yet to be adequately incorporated into the perspectives of psychological science. We also address traditions of communities of color that have become absorbed or consumed by psychological science but often after their cultural and historical origins are erased, like Buddhism. We locate these racial and scientific dynamics, and associated patterns of neglect and erasure, within a longstanding aversion in and by psychological science—here understood as a collective actor unto itself—to perspectives of people of color. Consequently, the promise not only of diversity, but of desegregation, has yet to be fulfilled within psychology. We conclude by discussing the psychosocial power of social movements—including South Africa's apartheid-related Truth and Reconciliation process as personally experienced by our second author—to suggest elements of pathways forward.